2017
DOI: 10.1371/journal.pgen.1006552
|View full text |Cite
|
Sign up to set email alerts
|

SBDS-Deficient Cells Have an Altered Homeostatic Equilibrium due to Translational Inefficiency Which Explains their Reduced Fitness and Provides a Logical Framework for Intervention

Abstract: Ribosomopathies are a family of inherited disorders caused by mutations in genes necessary for ribosomal function. Shwachman-Diamond Bodian Syndrome (SDS) is an autosomal recessive disease caused, in most patients, by mutations of the SBDS gene. SBDS is a protein required for the maturation of 60S ribosomes. SDS patients present exocrine pancreatic insufficiency, neutropenia, chronic infections, and skeletal abnormalities. Later in life, patients are prone to myelodisplastic syndrome and acute myeloid leukemia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 61 publications
2
41
0
Order By: Relevance
“…Extracts were then centrifuged at 10,000g for 10 min at 4 °C. The acid supernatant was neutralized with K 2 CO 3 and used for luminometric determination of ATP (ATP determination kit, Molecular Probes) using the method of Lundin (Lopez-Lluch et al, 2006) as modified in (Calamita et al, 2017).…”
Section: Atp Content Analysismentioning
confidence: 99%
“…Extracts were then centrifuged at 10,000g for 10 min at 4 °C. The acid supernatant was neutralized with K 2 CO 3 and used for luminometric determination of ATP (ATP determination kit, Molecular Probes) using the method of Lundin (Lopez-Lluch et al, 2006) as modified in (Calamita et al, 2017).…”
Section: Atp Content Analysismentioning
confidence: 99%
“…Accumulating evidence strongly suggests a ribosomal function of SBDS, as human SBDS could interact with certain ribosomal subunits and play an important role in ribosome maturation (Calamita et al, 2017; Huang and Shimamura, 2011). A recent report further supports the idea that SDS belongs to ribosomopathies because defective ribosome synthesis and protein translation insufficiency was observed in an SBDS-deficient mouse model (Tourlakis et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…For example, two of the most frequent disease-associated mutations are 183-184TA/→CT and 258+2T/→C, which result in two premature SBDS-truncated proteins with an in-frame stop codon (K62X) and a frameshift mutation (84Cfs3), respectively (Boocock et al, 2003). SBDS has been implicated in mRNA translation and ribosome biogenesis (Calamita et al, 2017; Ganapathi et al, 2007). Previous reports also suggest that SBDS may contribute to telomere regulation, because SDS and SBDS -mutated aplastic anemia (AA) patients have shorter telomeres (Calado et al, 2007; Thornley et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In Drosophila, we found that an overexpression of eIF6 leads to a reduction of the free 60S pool in eye imaginal discs, consistent with eIF6 biochemical activity. Such reduction could imply lower general translation, due to less availability of 60S subunits, as in the case of Sbds mutants 39 . Conversely, 60S could be already engaged with 40S into active translating 80S, thus heightening general translation.…”
Section: Discussionmentioning
confidence: 99%